The Scriptural Accounts of Creation and the Concept of Theistic Evolution - Opeloye, M. O. (2014)
The scriptures considered in this study are the Bible and the Q'uran. The doctrine of creation as enshrined in the two books (of Christianity and Islam) maintain respectively that the universe was not self creating, neither is it self - existing as it owes its origin and continued sustenance to the omnipotent power and the unconditional will of the Almighty God. The two scriptures' views on creation uphold the theory of creation ex nihilo (creation out of nothing) through supernatural fiat. This theory runs counter to the theory of emanation, which believes that the universe was made out of the substance of deity as contained in the Brahamic Sacred Books, as well as the theory that the universe was made out of something independent that either existed eternally or came spontaneously into being as contained in the cosmologies of the Greeks.